2019
DOI: 10.3390/ijms20081838
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing as Antivirulence Target in Cystic Fibrosis Pathogens

Abstract: Cystic fibrosis (CF) is an autosomal recessive genetic disorder which leads to the secretion of a viscous mucus layer on the respiratory epithelium that facilitates colonization by various bacterial pathogens. The problem of drug resistance has been reported for all the species able to colonize the lung of CF patients, so alternative treatments are urgently needed. In this context, a valid approach is to investigate new natural and synthetic molecules for their ability to counteract alternative pathways, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 246 publications
0
44
0
Order By: Relevance
“…Targeting QS is the most extensively studied alternative strategy and demonstrated against various multi-drug resistant pathogens. Since QSIs curb several virulence factors and biofilm without affecting growth unlike antibiotics, it leads to the attenuation of pathogenesis while preventing selective pressure and development of antibiotic resistance [18]. Hence, QS interference seems to be a promising approach to address there MDR pathogens and can be developed as standalone anti-infective drugs or in combination with conventional antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting QS is the most extensively studied alternative strategy and demonstrated against various multi-drug resistant pathogens. Since QSIs curb several virulence factors and biofilm without affecting growth unlike antibiotics, it leads to the attenuation of pathogenesis while preventing selective pressure and development of antibiotic resistance [18]. Hence, QS interference seems to be a promising approach to address there MDR pathogens and can be developed as standalone anti-infective drugs or in combination with conventional antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive understanding that P. aeruginosa and many other pathogens, control much of their virulence by QS, offered a new direction to a novel and robust "drug target" [14][15][16]. Many studies revealed that curbing QS would effectively reduce the biofilm formation and virulence [17][18][19]. Unlike conventional antibiotics, quorum sensing inhibitors (QSIs) will not kill the bacteria, rather they disarm the bacterial pathogenicity alone and hence they seem to have only slighter chances to get resistance [20].…”
Section: Introductionmentioning
confidence: 99%
“…Looking into studies concerning a disease scenario, the majority were CF related (Table 3). CF is a genetic disease associated with the dysfunction of a transmembrane chlorine channel that causes secretion of a viscous mucus layer on the respiratory epithelium that facilitates microbial colonisation, with lung disease being the major cause of reduced life expectancy and death in these patients (Scoffone et al 2019). Although S. aureus is typically one of the primary microorganisms isolated in CF lungs during early childhood, it is quickly followed by P. aeruginosa, which progressively increases its prevalence as patients grow older (Razvi et al 2009;Price et al 2013).…”
Section: Database and Knowledge Network Overviewmentioning
confidence: 99%
“…A new strategy to control the infections aims to affect and stop the adaptability of microbes to the host environment and prevent their communication with each other rather than affecting their growth. 1,2 Quorum sensing (QS) is defined as communication between cells that relies on the cells density and the concentration of specific signaling molecules known as the autoinducers (AIs). 2 AIs bind to their receptors forming a complex that will bind to a promoter and regulate the QS genes.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa contains four distinguished QS systems (Las, Rhl, Pqs and Iqs) that use AIs: N-oxododecanoyl-l-homoserine lactone (OdDHL or 3OC12-HSL), N-butanoyl-l-homoserine lactone (BHL or C4-HSL), the Pseudomonas quinolone signal (PQS), and the integrated quorum-sensing signal (IQS), respectively. 1,3 Once significant levels of these signals were reached, they control the transcriptional regulatory protein LasR, RhIR, and Pqs then virulence factors transcription was enhanced. 4 P. aeruginosa produces various pathogenicity factors and enzymes including pyocyanin, elastases, rhamnolipids, protease and extracellular exotoxin A that assist in microbial dissemination and interfere with the host immune system.…”
Section: Introductionmentioning
confidence: 99%